2014
DOI: 10.1007/978-3-319-05161-1_3
|View full text |Cite
|
Sign up to set email alerts
|

TRPs as Chemosensors (ROS, RNS, RCS, Gasotransmitters)

Abstract: The transient receptor potential (trp) gene superfamily encodes TRP proteins that act as multimodal sensor cation channels for a wide variety of stimuli from outside and inside the cell. Upon chemical or physical stimulation of cells, TRP channels transduce electrical and/or Ca(2+) signals via their cation channel activities. These functional features of TRP channels allow the body to react and adapt to different forms of environmental changes. Indeed, members of one class of TRP channels have emerged as senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 157 publications
1
42
0
Order By: Relevance
“…Melastatin and vanilloid subfamilies include TRP melastatin 2 (TRPM2) and TRP vanilloid 1 (TRPV1) Ca 2+ permeable cation channels49. Capsaicin (CAP) is a pungent component of hot chili peppers, and TRPV1 is activated by different stimuli, including CAP 10 and oxidative stress11. A growing amount of evidence has shown that ADPR is produced as a byproduct of NAD metabolism.…”
mentioning
confidence: 99%
“…Melastatin and vanilloid subfamilies include TRP melastatin 2 (TRPM2) and TRP vanilloid 1 (TRPV1) Ca 2+ permeable cation channels49. Capsaicin (CAP) is a pungent component of hot chili peppers, and TRPV1 is activated by different stimuli, including CAP 10 and oxidative stress11. A growing amount of evidence has shown that ADPR is produced as a byproduct of NAD metabolism.…”
mentioning
confidence: 99%
“…NO regulates TRP channels via cGMP/PKG-dependent phosphorylation. 119 Excessive ROS target multiple biomolecules, causing numerous cellular complications, including lipid peroxidation, protein oxidation/inactivation, and DNA damage/mutations. 117 Furthermore, increased O 2 − levels attenuate endothelium-dependent relaxation and enhance VSMC contraction through the formation of hydroxyl radicals.…”
Section: Physiological and Pathological Roles Of Rhokinase In The Carmentioning
confidence: 99%
“…Further studies have pointed out that reactive oxygen species (ROS) and reactive nitrogen species may change activities of voltage-gated Na + , Ca 2+ , and K + channels in the aging process 16. ROS and reactive nitrogen species also activated and potentiated the TRPV1 and TRPM2 cation channels 17,18. Whether oxidative stress is involved in the modulation of NaV1.7 and NaV1.8 activities under diabetic conditions is not known.…”
Section: Introductionmentioning
confidence: 99%